Mean barrier height and richardson constant for Pd/ZnO Thin film-based Schottky Diodes grown on n-Si substrates by thermal evaporation method - Somvanshi D.; Jit S. (My University, 2025)
This letter reports the temperature-dependent electrical parameters of Pd/n-ZnO thin film-based Schottky diodes grown on n-Si <100> substrates by thermal evaporation method. The parameters have been investigated by considering a Gaussian distributed barrier height across the Pd/n-ZnO interface with a standard deviation ?0 around a mean barrier height q?B,m· As compared with the reported results, the estimated values of the Richardson constant (∼19.54Acm-2 K-2) and mean barrier height (∼1.41 eV) are much closer to their theoretically predicted values of 32Acm-2K -2(for m*e =0.27m0 ) and 1.42 eV (for work function of Pd = 5.12 eV and electron affinity of ZnO = 3.7 eV), respectively. © 2013 IEEE.